Development of hypertensive complications in oocyte donation pregnancy: protocol for a systematic review and individual participant data meta-analysis (DONOR IPD) - Saskia le Cessie; Marie-Louise van der Hoorn; Jan van Lith; Eileen Lashley; Kim van Bentem (BMJ Open)
Introduction The assisted reproductive technique of oocyte donation (OD) is comparable to in vitro fertilisation (IVF), with the distinction of using a donated oocyte and thus involving two women. Compared with IVF and naturally conceived (NC) pregnancies, OD pregnancies have a higher risk for pregnancy complications as pregnancy-induced hypertension (PIH) and pre-eclampsia (PE). Various covariates among women pregnant by OD, however, also contribute to an increased risk for developing hypertensive complications. Therefore, we will conduct the DONation of Oocytes in Reproduction individual participant data (DONOR IPD) meta-analysis to determine the risk for the development of hypertensive complications in OD pregnancy, in comparison to autologous oocyte pregnancy (non-donor IVF/intracytoplasmic sperm injection (ICSI) and NC pregnancy). The DONOR IPD meta-analysis will provide an opportunity to adjust for confounders and perform subgroup analyses. Furthermore, IPD will be used to externally validate a prediction model for the development of PE in OD pregnancy.Methods and analysis A systematic literature search will be performed to search for studies that included women pregnant by OD, and documented on hypertensive complications in OD pregnancy. The authors from each study will be asked to collaborate and share IPD. Using the pseudoanonymised combined IPD, we will perform statistical analyses with one-stage and two-stage approaches, subgroup analyses and possibly time-to-event analyses to investigate the risk of developing hypertensive complications in OD pregnancy. Furthermore, we will formally assess a prediction model on its performance in an external validation with the use of IPD.Ethics and dissemination Ethical approval and individual patient consent will not be required in most cases since this IPD meta-analysis will use existing pseudoanonymised data from cohort studies. Results will be disseminated through peer-reviewed journals and international conferences.PROSPERO registration number CRD42021267908.